Comparative in vivo constituents and pharmacokinetic study in rats after oral administration of ultrafine granular powder and traditional decoction slices of Chinese Salvia. (22nd October 2018) - Zhi, Haijuan; Li, Zhenwei; Deng, Yanping; Qi, Peng; Hou, Jinjun; Deng, Wen; Cheng, Jinle; Wu, Wanying; Guo, Dean
Abstract: Salvia miltiorrhiza, one of the most well‐known herbal medicines, is commonly used for the treatment of coronary heart diseases in China. Besides traditional decoction slices (TDS), another relatively new product of S. miltiorrhiza, ultrafine granular powder (UGP; D90 < 45 μm), is also increasingly being used. In this paper, a UHPLC‐LTQ‐Orbitrap MS technique was developed for a metabolite profile study after oral administration of UGP and TDS of S. miltiorrhiza . The results showed that the number of in vivo absorbed compounds from UGP was much greater than that from TDS, and different types of products from S. miltiorrhiza will have different metabolic processes in vivo . Furthermore, a UHPLC‐Q‐Trap MS/MS method for simultaneously determining four tanshinones (tanshinone IIA, dihydrotanshinone I, tanshinone I and cryptotanshinone) was established and applied to assess the pharmacokinetics of the two types of products. All of the analytes displayed significant higher area under the concentration–time curve and peak concentration after oral administration of UGP than after TDS, indicating that ultrafine powder product could improve the bioavailability and absorption of cryptotanshinon, tanshinone II A, dihydrotanshinonE I and tanshinone I in vivo . The present study provides scientific information for further exploration of the pharmacology of these two types of S. miltiorrhiza and offers a reference for clinical administration of S. miltiorrhiza .